Eco-Management and Eco-Standardization in Russia: The Perspectives and Barriers for Development - RATNER, Svetlana; IOSIFOV, Valery (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017DO - 10.14505//jemt.v8.1(17).23, 2017)
The Krasnodar Region is one of Russia's few traditional centers of tourism. The 2014 Winter Olympics in Sochi contributed to rapid development of the tourist infrastructure in the region, as well as its increased attractiveness to Russian and international tourists. An enlarged flow of tourists requires the fast development of an effective environmental policy, aimed at maintaining the quality of ecosystems in developing tourist territories. In Russia, the environmental labeling of hotels and other accommodation facilities is not yet widespread. Therefore, the main purpose of this study is to analyze the existing national regulatory framework (federal and regional legislation, standards, and voluntary certification systems, including regional ones) for identification of the most advanced ecology-preserving legal acts, which could serve as a prototype for the development of a regional system for eco-labeling in the tourist business. Secondly, we aim to analyze the attractiveness of eco-hotels for Russian tourists and their readiness to pay to for the different services in eco-hotels. To do so, we use face-to-face surveys, and process the obtained empirical data further using the methods of non-parametrical statistics. The results of the survey show that the majority of respondents (who are also tourists that visit the region on a regular basis), are poorly informed of the issues of ecologic management and ecologic labeling, as well as the issue of how intensive tourism affects the regional ecology. However, the majority of respondents still show interest in eco-hotel services, and would rather prefer to stay there if the price and the overall quality of their stay remains the same.